SURGICAL CORRECTION OF THE UPPER EYELID: CLINICAL EXPERIENCE AND ANALYSIS OF RESULTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article presents the experience of performing upper blepharoplasty in the plastic surgery department of the Tashkent Medical Academy's multidisciplinary clinic for the period 2020-2024. An analysis of 320 cases of surgical correction of the upper eyelid was conducted, taking into account the anatomical, age-related, and functional characteristics of the patients. Indications for surgery, marking methods, and stages of surgical intervention are described. Special attention is given to the principles of preoperative preparation and individualization of surgical approach. The importance of a comprehensive approach to the correction of the periorbital area for achieving aesthetic and functional results is emphasized. The presented data confirm the high effectiveness of the technique, provided that the standardized patient management algorithm is followed.